2001
DOI: 10.1016/s0030-4018(01)01292-5
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the recording dynamics of phenanthrenequinone-doped poly(methyl methacrylate) materials

Abstract: A comparative analysis of phenanthrenequinone-doped poly(methyl methacrylate) materials fabricated at California Institute of Technology and National Chiao Tung University is performed in order to understand the dierences exhibited in their recording and baking dynamics. Ó 2001 Published by Elsevier Science B.V.Keywords: Holography; Photopolymer material; PQ-PMMA; Grating dynamics; Temperature eect Phenanthrenequinone-(PQ-) doped poly(methyl methacrylate) (PMMA) [1,2] has been used as a recording material in o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 5 publications
0
33
0
Order By: Relevance
“…In holographic recording, the writing time is in the order of 1000 min. The diffusion length of PQ molecules in PMMA matrix at room temperature can be calculated to be in the order of submicrometers, [30][31][32] which is a fraction of typical fringe spacing of the interference fringe. Hence, the spatial modulation of the hologram will be affected.…”
Section: Investigations On the Twp Holographic Recordingmentioning
confidence: 99%
“…In holographic recording, the writing time is in the order of 1000 min. The diffusion length of PQ molecules in PMMA matrix at room temperature can be calculated to be in the order of submicrometers, [30][31][32] which is a fraction of typical fringe spacing of the interference fringe. Hence, the spatial modulation of the hologram will be affected.…”
Section: Investigations On the Twp Holographic Recordingmentioning
confidence: 99%
“…We also note that the amount of MMA remaining in the material layer can affect the behavior of the material. In a previous paper it was reported that PQ can act as photointiator of polymerization, where there is a significant excess of residual monomer [21]. In this case, the photoactivated PQ molecules act as initiators of the polymerization before they eventually attach to MMA, which can produce a substantial modulation of the index of refraction [21].…”
Section: Introductionmentioning
confidence: 98%
“…It is important to note that the process used to produce the layers, (not only their composition) can have dramatic impact on how it reacts during exposure. For example the use of spin coating out of a solvent like toluene, bulk polymerized in a mold, or free radical polymerization at multiple conditions [21], will all lead to different responses. However we also wish to emphasize that while the simulations performed in this paper are carried out using physical parameter values from [13,14], the results presented should be of at least qualitative relevance for PQ/PMMA materials in general (not just a specific type).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations